Assessing the Safety of Craniotomy for Resection of Primary Central Nervous System Lymphoma: A Nationwide Inpatient Sample Analysis - Yun, Jonathan; Yang, Jingyan; Cloney, Michael; Mehta, Amol; Singh, Suprit; Iwamoto, Fabio Massaiti; Neugut, Alfred I.; Sonabend, Adam M. (Frontiers in Neurology, 2017)
Background: Unlike many other central nervous system (CNS) tumors, the surgical management of primary central nervous system lymphomas (PCNSL) is traditionally limited by diagnostic biopsy. Studies that predate the use of modern neurosurgical techniques have reported a prohibitive operative morbidity for this surgery. These early experiences have dictated the non-surgical management of PCNSL, whereas resection for cytoreduction is a mainstay of treatment in other CNS malignancies. Recent studies have suggested that craniotomy with the goal of cytoreduction might be associated with a favorable overall and progression-free survival for some patients with PCNSL. To challenge the traditional non-surgical paradigm, it is essential to first investigate the safety of resection for PCNSL. Methods: To determine the operative morbidity of resection for this disease, we performed a population-based assessment of complications using the Nationwide Inpatient Sample (NIS) database for the years 1998-2013 for biopsies and open craniotomies for PCNSL and other brain tumors. Results: Among 95 patients who underwent biopsy and 34 patients who underwent craniotomy, we found no significant difference in complication rates between craniotomy for resection and biopsy procedures for PCNSL (23.16% vs. 20.59%). The types of complications differ between diagnoses, with the PCNSL cohort suffering mainly medical complications and the non-PCNSL cohort suffering mainly from neurological complications. Conclusions: These findings support the safety of craniotomies in PCNSL, and help provide a rationale for future prospective studies to evaluate the safety and efficacy of resection for this disease.